A review on covalent organic frameworks as adsorbents for organic pollutants. (10th May 2023) - Aslam, Awais Ali; Irshad, Adnan; Nazir, Muhammad Shahid; Atif, Muhammad
Abstract: Covalent organic frameworks (COFs) have attained substantial attention as promising candidate for pollutant adsorption due to extraordinary behavior in tunable porosity, large surface area, high crystallinity, reusability and surface chemistry. The data in this review has been compiled regarding mechanistic approaches of COFs towards adsorption of a variety of organic pollutants, including pharmaceutical, pesticides, dyes, and industrial waste. In addition, adsorption performance comparison has also been made between COFs and other materials. This review has latest data on the topic to understand and resolve present as well as future challenges. Graphical abstract: Image 1